Why onchocerciasis transmission persists after 15 annual ivermectin mass drug administrations in South-West Cameroon. Issue 1 (11th January 2021) - Forrer, Armelle; Wanji, Samuel; Obie, Elisabeth Dibando; Nji, Theobald Mue; Hamill, Louise; Ozano, Kim; Piotrowski, Helen; Dean, Laura; Njouendou, Abdel J; Ekanya, Relindis; Ndongmo, Winston Patrick Chounna; Fung, Ebua Gallus; et al.
Abstract : Introduction: Onchocerciasis is targeted for elimination mainly with annual community-directed treatment with ivermectin (CDTI). High infection levels have been reported in South-West Cameroon, despite ≥15 years of CDTI. The aim of this study was to assess factors associated with continued onchocerciasis transmission and skin disease. Methods: A large-scale cross-sectional study was conducted in 2017 in 20 communities in a loiasis-risk area in South-West Cameroon. A mixed-methods approach was used. Associations between infection levels, skin disease and adherence to CDTI were assessed using mixed regression modelling. Different community members' perception and acceptability of the CDTI strategy was explored using semi-structured interviews. Results: Onchocerciasis prevalence was 44.4% among 9456 participants. 17.5% of adults were systematic non-adherers and 5.9% participated in ≥75% of CDTI rounds. Skin disease affected 1/10 participants, including children. Increasing self-reported adherence to CDTI was associated with lower infection levels in participants aged ≥15 years but not in children. Adherence to CDTI was positively influenced by perceived health benefits, and negatively influenced by fear of adverse events linked with economic loss. Concern of lethal adverse events was a common reason for systematic non-adherence. Conclusion: CDTI alone is unlikely to achieve elimination in those high transmission areas where low participation is commonly associated with the fear of adverse events, despite the current quasi absence of high-risk levels of loiasis. Such persisting historical memories and fear of ivermectin might impact adherence to CDTI also in areas with historical presence but current absence of loiasis. Because such issues are unlikely to be tackled by CDTI adaptive measures, alternative strategies are needed for onchocerciasis elimination where negative perception of ivermectin is an entrenched barrier to community participation in programmes.